Preconceito e retórica: o feminino na música popular brasileira - Trepiccio, Thatyane (2009)
This work establishes itself in the research s line text and speech in the verbal and writing modalities and it shows as theme the feminine in the Brazilian pop music. The reason of research due to the fact that in our society there is a initiate prejudice against blonde women. Therefore, our general objective is prove that this prejudice is minimized in the mass pop music, since the predominance be of a positive ethnos. The work s evolution, is based in the notion of Aristóteles rhetoric and in basic precepts about the rhetoric recourse cited especially in Perelman e Tyteca, Reboul, Tringali and Meyer. Starting from biblical and mythological figures of Lilith, Eva and Aphrodite is done a comparison with the ethos of eternalized women by the history and by the modern women cited in the songs. The realized research, in the twenty-five samples, allows the identification of the several ways as the blonde woman can be seen in the Brazilian pop music: fatal, stupid, delicate, charm, grifter and desirable. Having as base the ethos above formed in the studied songs, we reach a conclusion, according the sample s numbers, that the blonde woman is dear for the men and awakes the desire, a passion that can be contained in the love, that so did the mithological figure of Aphrodite that charmed casting just the glance